Review of Yunte Huang, Charlie Chan: The Untold story of the Honorable Detective and his rendezvous with American history - Ferguson, Jonathan (Studia Orientalia Electronica, 2014)
This is a book review of a monograph by Yunte Huang on the literary/cinematic figure of Charlie Chan, the Chinese-American detective. The trope of Charlie Chan is a controversial one, but Huang takes into account the ambivalent and ambiguous character of the trope, while reflecting on Huang’s own positionality as a Chinese-American. Huang also contextualises Charlie Chan himself; speaking of the author Earl Derr Biggers (who created Chan); as well as of Chang Apana, the real-life inspiration for the figure.